Microbial Etiology and Antibiotic Susceptibility of Samples from Neonatal Intensive Care Units Patients in a Tertiary Care Center in Iran - Samaneh Salarvand; Alireza Abdollahi; Pegah Afarinesh Khaki; Mahsa Norouzi Shadehi; Hossein Dalili; Saeed Nateghi; Zahra Panahi; Elham Nazar (Iranian Journal of Neonatology)
Background: Bacterial infection among neonatal patients admitted to the neonatal intensive care unit (NICU) is a global crisis and is among the first causes of neonatal mortality globally. Hence, this study aimed to evaluate the prevalence of bacterial pathogens from collected samples of neonatal infection in the NICU of a tertiary care center in Tehran, Iran. Methods: In this study, we used data from blood, ulcer/fluids, and urine samples of NICU neonates at Imam Khomeini Hospital from 2019 to 2022. Results: Overall, 712 urine cultures (144 positives), 4578 blood cultures (376 positives), and 1771 ulcer/fluid cultures (411 positives) were gathered. Among positive blood cultures, the most prevalent bacterial species was Klebsiella pneumonia (120, 32.88%). Among urine cultures, the most prevalent bacterial species was Klebsiella pneumonia (71, 49.31%). Among positive ulcer/fluid cultures, the most prevalent bacterial species were Coagulase Negative Staphylococci (150, 36.49%). The highest sensitivity of Klebsiella pneumonia was against Ciprofloxacin (15.83%) in blood samples and resistant to Gentamycin (81.67%). Among urine samples, the highest sensitivity of Klebsiella pneumonia was against Ciprofloxacin (29.58%%) and the highest resistance against Gentamycin (84.51%). Among the ulcer/fluid samples, the highest sensitivity of Coagulase Negative Staphylococci was against Ciprofloxacin (13.48%) and the highest resistance against Cotrimoxazole (14.81%). Conclusion: The most prevalent bacterial species found were Klebsiella pneumonia and Coagulase Negative Staphylococci. These species showed high resistance against multi drugs such as Cotrimoxazole, Ampicillin-sulbactam, and Piperacillin-tazobactam. National health policymakers should focus on surveillance programs to control and monitor such trends in antibiotic resistance.